Bibliometric analysis and multi-criteria decision-making (MCDM) approach for ranking passive design strategies in hot climates - Emad S. Mushtaha; Vittorino Belpoliti; Aseel Ali Hussien; Ahmed Abdeen; Aref Maksoud; Chaouki Ghenai; Imad Alsyouf; Abbas A. Almualim; Rawan Hamad; Lama Alhaj Husein (Results in Engineering)
With the pressing Climate Change challenges, passive design strategies are seen as vital for reducing energy consumption in buildings and to address the negative impact of buildings on the natural environment. This work present a novel approach by establishing weighted values for each passive design strategies to be investigated using questionnaire for residential buildings in hot climates. A bibliometric analysis and an extensive literature review of hot climate-based studies that address the effectiveness of passive building measures was conducted. Climate Consultant software was used to conduct a comprehensive overview of the existing passive practices to control energy consumption while providing thermal comfort for buildings’ users. Three main criteria have been derived to address all aspects of passive design: environmental design, building design, and building construction factors. Sub-criteria for the categories were developed for subjective and objective evaluations. A questionnaire was distributed among 36 academic experts and practitioners of varying professional experiences. Criteria’s weighted values were determined using multi-criteria decision making (MCDM), specifically the analytic hierarchy process (AHP) using Expert Choice software. Furthermore, a sensitivity analysis was carried out to analyze the results. The findings suggest that factors ''Thermal insulation,'' ''Building orientation/openings,'' and ''Window shading devices'' are among the top-rated with priority weight of 6.7%, 6.4%, and 6.1%, respectively. . It is recommended that these passive design strategies be optimized as a common practice in conjunction with design components.